ANALISIS PEBEDAAN RANTAI PASAR BERAS ORGANIK DAN BERAS ANORGANIK DI DESA GENTUNGAN KECAMATAN MOJOGEDANG KABUPATEN KARANGANYAR - HERIYANTO HERIYANTO; M.TH HANDAYANI; SUSWADI SUSWADI; KUSRIANI PRASETYOWATI (JURNAL ILMIAH AGRINECA, 2019)
The purpose of this study was to determine the analysis of differences in organic rice and inorganic rice market chains in the study area and to explain differences in marketing functions carried out by farmers and each organic rice institution with inorganic rice in the study area. The location of the study was carried out by purposive sampling (deliberate), the research sample was taken using descriptive analytical method. The data used are primary data and secondary data in the research area through direct interviews with farmers using questionnaires. This study uses simple calculations with formulas - the formula according to market chain theory. The results of the analysis show that the organic rice market chain in the study area contains two organic rice market chains, namely 1. Organic rice farmers - Collector traders - Large traders - Out of town and an inorganic rice market chain 2. Organic rice farmers - Collector traders - Retail traders - Consumer. The inorganic rice market chain in the study area is inorganic rice farmers - collectors - wholesalers - consumers. Every marketing institution involved in the market chain of organic rice and inorganic rice performs different functions. The total marketing cost of the chain I for organic rice is Rp. 1,675 per kg, the total cost of chain chain II organic rice is Rp. 1,170 per kg and for the total marketing costs of inorganic rice Rp. 7,90 per kg. In channel I organic rice has a total margin of Rp.3,000 per kg, channel II organic rice has a margin of Rp.2,000 per kg and an inorganic rice channel has a margin of Rp.1,200 per kg. Total profit of organic rice channel I Rp. 1,325 per kg, the total profit of organic rice channel II is Rp. 1,330 per kg while the total profit of the inorganic rice channel is Rp. 4,10 per kg. Farmer’s Share on organic rice channel I was 76.92%, organic rice channel II was 80.00% and inorganic rice channel was 86.67%. Marketing channel II organic rice is the most efficient because on channel II retailers do not issue marketing costs but have a farmer’s share value of 80.00% with a marketing margin of Rp.2,000 per kg and a profit of Rp. 1,330 per kg. The organic and inorganic rice market chain is said to be efficient.